The Pedagogy of the Imagination (LEARNing Landscapes, 2009)
The author takes an essay on the imagination by Italo Calvino as the cue for a reconsideration of the role of imagination in children’s thought and action and its educational implications. He emphasizes the value of interpretation, or critical scrutiny, as foremost among a teacher’s skills and central to curriculum design, teaching method and educational assessment, demonstrating the quality of children’s imaginative work, and how to value it, by means of a close reading of an eight year old’s brief med- itation on coming to school for the first time.
Keywords: imagination; interpretation; critical scrutiny; curriculum; teaching method; asessement method